Front-End Design for Non-Invasive Electrical Resistance Tomography for Liquid Column - Wahab Y.A.; Rahim R.A.; Zawawi M.A.; Rahiman M.H.F.; Ling L.P.; Goh H.; Aw S.R.; Rahim H.A.; Juliza Jamaludin (Universiti Teknikal Malaysia Melaka, 2024)
Indexed by Scopus